CLEC5A is a critical receptor in innate immunity against Listeria infection - Szu-Ting Chen (Nature Portfolio, 2017)
The lectin receptor CLEC5A is a pattern recognition receptor that has been shown to detect dengue and Japanese encephalitis virus. Here the authors show that CLEC5A is needed for optimal ROS production, NET formation and other immune responses to Listeria monocytogenes in mice.